2010
DOI: 10.1007/s11661-010-0326-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solute Atoms on Aluminum Grain Boundary Sliding at Elevated Temperature

Abstract: Grain boundary sliding (GBS) is an important deformation mechanism for elevated temperature forming processes. Molecular dynamics simulations are used to investigate the effect of solute atoms in near grain boundaries (GBs) on the sliding of Al bicrystals at 750 K (477°C). The threshold stress for GBS is computed for a variety of GBs with different structures and energies. Without solute atoms, low-energy GBs tend to exhibit significantly less sliding than high-energy GBs. Simulation results show that elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…In this regard, yttrium is expected to be more effective than aluminum in suppressing GBS. However, Du et al [23] concluded that the size difference alone cannot account for the marked differences in GBS. They suggested that the chemistry at grain boundaries through solute alloy additions is more important than atomic size; that is, the atomic interaction between solute atoms and host atoms plays an important role in controlling GBS.…”
Section: Significance Of Alloying Constituent In Superplastic Magnesimentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, yttrium is expected to be more effective than aluminum in suppressing GBS. However, Du et al [23] concluded that the size difference alone cannot account for the marked differences in GBS. They suggested that the chemistry at grain boundaries through solute alloy additions is more important than atomic size; that is, the atomic interaction between solute atoms and host atoms plays an important role in controlling GBS.…”
Section: Significance Of Alloying Constituent In Superplastic Magnesimentioning
confidence: 99%
“…On the other hand, little is known about the effect of solid solution alloying on grain boundary relaxation and GBS. For example, it has been reported that grain boundary relaxation in aluminum alloys is influenced by the alloying elements; small additions of zinc, silver, copper and germanium that form solid solutions with aluminum have no significant effect on grain boundary relaxation, whereas magnesium effectively suppresses grain boundary relaxation [18], although conclusions are sometimes contradictory [23]. Molecular dynamics simulations of GBS in bicrystal copper have shown that the degree of GBS in random high-angle grain boundaries is reduced by the addition of larger substitutional atoms [24].…”
Section: Introductionmentioning
confidence: 99%
“…34 As shown in Figure 5b, magnesium solutes increased t o of all grain boundaries because they formed immobile clusters with surrounding aluminum atoms due to the negative heat of formation of magnesium and aluminum. However, silicon solute atoms decreased (by approximately a factor of two) the sliding threshold in lowenergy grain boundaries by weakening aluminum bonds, increasing the mobility of the surrounding aluminum atoms, and consequently enhancing grain boundary diffusivity.…”
Section: Materials Design Opportunities and Challengesmentioning
confidence: 91%
“…In the fi eld of materials science, this method is now being applied to simulate the evolution of microstructure and defects in aluminum alloys, including precipitation, dislocation reactions and so on (Du et al , 2009;Stegailov et al , 2009).…”
Section: Modeling Technologymentioning
confidence: 99%